Kemampuan Mengingat Katakana Pada Siswa SMA Negeri 1 V Koto Kampung Dalam - Nadia Fajriati; Damai Yani (Universitas Negeri Padang, 2025)
In Japanese language learning, kana letters (consisting of hiragana and katakana) are basic components that students must master to understand the structure and reading of Japanese. Based on the results of observations and interviews between researchers and Japanese language teachers at SMA Negeri 1 V Koto Kampung Dalam, it is known that many students still find it difficult to remember katakana letters consisting of seion, dakuon, and yoon. Meanwhile, the teacher has a target that grade XI students must master katakana letters after mastering hiragana letters in grade X. The purpose of this study was to determine the ability to remember and use seion and yoon in grade XI.F7 students at SMA Negeri 1 V Koto Kampung Dalam. This type of research is quantitative research. This research is a descriptive quantitative research using descriptive statistical techniques. Data were taken from a total sampling of class XI IIS A to XI IIS F totaling 26 students. The results of this study indicate that most grade XI students at SMA Negeri 1 V Koto Kampung Dalam have good ability to remember Katakana, with an average score of 83.03. As many as 65.38% of students managed to achieve the Minimum Completion Criteria (KKM) of 76, which indicates that the majority of students have mastered the material well, while 34.62% of students are still below the KKM. This shows that there is a difference in mastery of the material between students. In addition, it is also known that the average value for the katakana seion indicator is 83.46, and for katakana yoon 82.69, which shows that the mastery of the material in both indicators is in line.